Unemployment, total factor productivity, budget deficit and wage share in South Africa - Juniours Marire (Economic Journal of Emerging Markets, 2022)
Purpose ― The paper investigated the effect of the interaction of fiscal deficits and total factor productivity (TFP) and fiscal deficits and the wage share on unemployment.